The Effect of Water Immersion on the Shear Bond Strength Between Chairside Reline and Denture Base Acrylic Resins - Andrea Azevedo, DDS;1 Ana Lucia Machado, DDS, MS, PhD;2 (Journal of Prosthodontics, 2007)
The effect of water immersion on the shear bond strength (SBS) between 1 heatpolymerizing acrylic resin (Lucitone 550-L) and 4 autopolymerizing reline resins (Kooliner-K, New Truliner-N, Tokuso Rebase Fast-T, Ufi Gel Hard-U) was investigated. Specimens relined with resin L were also evaluated.